Heat health risk assessment and identification of priority control areas in residential communities of Shijiazhuang - Shikai Song; Shikai Song; Shikai Song; Yanrui Shang; Leibin Wang; Leibin Wang; Leibin Wang; Qiang Liu; Qiang Liu; Yuanjie Zhao (Frontiers in Public Health, 2025)
IntroductionUnder global warming, urban dwellers have been at significant health risk due to urban heat islands and frequent extreme heat events in recent years. Most previous assessments of heat health risk focused on the regional scale. Therefore, we aim to evaluate the fine level heat health risk of Shijiazhuang, China.MethodsResidential community was as choose as basic evaluation unit. The heat health risks of 1,086 residential communities in the main urban area of Shijiazhuang were assessed by the risk framework of the IPCC, in which the risk was multiplicatively aggregated by hazard, exposure, and vulnerability.ResultsIn 2023, the hazard followed a center-periphery pattern with decreasing value from the city center to the periphery, whereas vulnerability presented the opposite trend. This pattern aligned with the finding that hazard-dominant risk residential communities were generally distributed close to the center and the vulnerability-dominant risk appeared primarily near the periphery. Five villages some distance from the city center were evaluated to present very high risk, with vulnerability as the dominant risk factor. Two of the five villages were identified as priority control communities, and increasing the percentage of water bodies and vegetation was the most practical way to lower the heat health risk.DiscussionThe differences in population exposure indicator may greatly affects the stability of heat risk mapping output. The results can assist urban managers in gathering comprehensive information about the heat health risk and developing effective mitigation strategies.